Baseline susceptibility and cross-resistance of cycloxaprid, a novel cis-nitromethylene neonicotinoid insecticide, in Bemisia tabaci MED from China. (August 2018) - Wang, Ran; Fang, Yong; Mu, Changqing; Qu, Cheng; Li, Fengqi; Wang, Zhenyu; Luo, Chen
Abstract: The tobacco whitefly Bemisia tabaci (Gennadius) is an important crop pest which threatens agriculture worldwide. It has evolved resistance to various classes of insecticides. Cycloxaprid is a new-generation neonicotinoid which is a (nitromethylene) imidazole analogue of imidacloprid which is highly efficient for the control of various Hemipteran pests in China. Studies were conducted to determine the baseline susceptibility to cycloxaprid of 18 field samples of B. tabaci collected from 9 geographical locations in China and the possibility of cross-resistance between cycloxaprid and other important neonicotinoids of one laboratory-selected resistant strain. The 50% lethal concentrations (LC50 ) of cycloxaprid to these 18 samples ranged from 0.84 to 12.17 mg/L. Furthermore, compared with the susceptible laboratory strain, the imidacloprid-resistant strain exhibited a 27.9-fold resistance to imidacloprid and lower level of cross-resistance to acetamiprid (16.3-fold), thiacloprid (13.7-fold) and nitenpyram (16.6-fold), but no cross-resistance to cycloxaprid (1.9-fold). These results demonstrate that cycloxaprid could be one effective alternative insecticide for whitefly management that could reduce imidacloprid selection pressure. Highlights: We reported the first baseline susceptibility of cycloxaprid from China. 18 samples of B. tabaci MED from China exhibited relatively high susceptibility to cycloxaprid. The absence of cross-resistance between cycloxaprid and imidacloprid was showed in this study.